2005
DOI: 10.1021/np040174k
|View full text |Cite
|
Sign up to set email alerts
|

Manoyl Oxide Diterpenoids from Grindelia scorzonerifolia

Abstract: Two new norditerpenoids, 4beta-hydroxy-19-normanoyl oxide (1) and 4alpha-hydroxy-18-normanoyl oxide (2), the new 18-O-alpha-l-arabinopyranosylmanoyl oxide (3a), and the known diterpenoids jhanol (4) and 18-hydroxy-13-epi-manoyl oxide (5) were isolated, together with other common plant constituents from an Argentine collection of Grindelia scorzonerifolia. The structures of the new compounds were established by extensive 1D and 2D NMR techniques and chemical transformations. Structural features of compounds 2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 20 publications
2
20
0
1
Order By: Relevance
“…To our knowledge, this is the first time that 8,15-epoxylabdane has been found as a natural product (usually, the epoxy link is C-8 and C-13 or C-9 and C-13) (Ziegler and Spiteller, 1992;Carreras et al, 1996;Mebe, 2001;Ybarra et al, 2005;Argyropoulou et al, 2009).…”
Section: Resultsmentioning
confidence: 89%
“…To our knowledge, this is the first time that 8,15-epoxylabdane has been found as a natural product (usually, the epoxy link is C-8 and C-13 or C-9 and C-13) (Ziegler and Spiteller, 1992;Carreras et al, 1996;Mebe, 2001;Ybarra et al, 2005;Argyropoulou et al, 2009).…”
Section: Resultsmentioning
confidence: 89%
“…The 1 H and 13 C NMR spectroscopic data (Tables 1 and 2) of 7 resembled those of 18-hydroxy-13-epimanoyl oxide. 17 The major difference was that the methyl H 3 -17 signals and methylene group H 2 -12 signals in the known compound were replaced by the oxymethylene group H 2 -17 signals (d H 3.00 and 3.36, d, J ¼ 11. 1 Hz,each 1H;4.28 and 4.44,d,J ¼ 12.4 Hz,each 1H;d C 63.9) and the oxymethine group H-12 signals (d H 4.09, t, J ¼ 3.5 Hz, 1H; d C 69.3) in 7.…”
Section: Resultsmentioning
confidence: 99%
“…The 1 H-1 H COSY experiment showed connectivity of three moieties: I: 1 CH 2 -2 CH 2 -3 CH 2 ; II: 5 CH-6 CH 2 -7 CH 2 ; and III: 9 CH-11 CH(O)-12 CH 2 . The HMBC correlations from CH 3 -19 (d H 0.79, 3H, s) to C-3 (d C 35.1), C-5 (d C 44.4), and C- 18 (d C 15.7); from H [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]each 1H,d,J ¼ 11.2 Hz) to C-3, C-5, and C-19 (d C 17.7); and from H 2 -2 (d H 1.50 and 1.60, each 1H, m) to C-4 (d C 37.5) indicated that C-4 connected units I and II together. The HMBC correlations from CH 3 -20 (d H 0.96, 3H, s) to C-1 (d C 41.4), C-5, and C-9 (d C 66.0) and from H 2 -1b (d H 0.96, 1H, m) to C-9 suggested that C-10 (d C 35.9) connected units I and III together.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations